2019
DOI: 10.3390/molecules24193566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Aryl O-, C-, and S-Mannopyranosides as Potential Adhesion Inhibitors toward Uropathogenic E. coli FimH

Abstract: A set of three mannopyranoside possessing identical 1,1′-biphenyl glycosidic pharmacophore but different aglyconic atoms were synthesized using either a palladium-catalyzed Heck cross coupling reaction or a metathesis reaction between their corresponding allylic glycoside derivatives. Their X-ray structures, together with their calculated 3D structures, showed strong indicators to explain the observed relative binding abilities against E. coli FimH as measured by a improved surface plasmon resonance (SPR) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 52 publications
(91 reference statements)
1
18
0
Order By: Relevance
“…Para-substituted biphenyl derivatives were shown to be particularly appealing, owing to their numerous favorable binding interactions within the tyrosine gate. Thus, the structural and functional analyses of a series of O-, C-, and S-linked mannoside derivatives, incorporating the 1,1 -biphenyl pharmacophore and diverse aglycone atoms, demonstrated the suitability of these antagonists, establishing the possibility of further exploring these chemically modified mannosides [101,102]. Furthermore, it was shown that the biphenyl group linked to mannosides can be efficiently absorbed if orally administered [54,88].…”
Section: Fimh Antagonists Biochemical Characteristics and Bioavailabmentioning
confidence: 96%
See 1 more Smart Citation
“…Para-substituted biphenyl derivatives were shown to be particularly appealing, owing to their numerous favorable binding interactions within the tyrosine gate. Thus, the structural and functional analyses of a series of O-, C-, and S-linked mannoside derivatives, incorporating the 1,1 -biphenyl pharmacophore and diverse aglycone atoms, demonstrated the suitability of these antagonists, establishing the possibility of further exploring these chemically modified mannosides [101,102]. Furthermore, it was shown that the biphenyl group linked to mannosides can be efficiently absorbed if orally administered [54,88].…”
Section: Fimh Antagonists Biochemical Characteristics and Bioavailabmentioning
confidence: 96%
“…It has been shown that O-and C-linked α-d-mannosides with hydrophobic and aryl substituents are potent E. coli FimH antagonists, having an affinity in the same range as that of nanomolar [101]. Indeed, the conformation and lipophilicity of aglycone moieties, their position with respect to the core sugar structure and the type of chemical group determine the RIP of antagonist molecules [61,80].…”
Section: Fimh Antagonists Biochemical Characteristics and Bioavailabmentioning
confidence: 99%
“…For this reason, molecules able to interfere with bacterial virulence mechanisms have been proposed to combat UPEC infections [20]. Accordingly, FimH antagonists, such as d-mannose and its derivatives, have emerged as anti-virulence therapeutic strategies for the treatment of UTIs [21][22][23][24][25][26][27]. d-mannose, a C-2 epimer of d-glucose, as well as d-mannose-analogs, prevent FimH-mediated bacterial adhesion through a competitive inhibition mechanism [18,21,22,24,28].…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of biphenyl derivatives may provide additional advantages for the FimH antagonist molecule. The addition of 1,10-biphenyl pharmacophore and various aglycone atoms enhanced the alpha- d -mannose derivatives’ suitability as FimH inhibitors [ 59 , 60 ]. Further, glycomimetics based on mannose scaffolding has also been synthesized and widely studied for their aptitude as FimH antagonists [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%